TINGKAT PENERIMAAN KONSUMEN PRODUK SOSIS KORO PEDANG DI KABUPATEN JEMBER - Rizaldi Adhisky; Bambang Heri Purnomo; Ahmad Nafi' (Agroindustrial Technology, University of Trunojoyo Madura, 2018)
Sausage is a pulverized meat mixed with herbs or spices and then inserted and formed in a wrapper or casing. The ingredients used for the manufacture of sausages are meat, fat, binder, filler, water, salt and seasoning. Today has been produced sausage with non-meat raw materials, one example is by using the raw material in the form of koro pedang. Koro pedang have many advantages, one of which is to reduce the consumption of food made from raw meat. This is because the production of meat in Indonesia is low and must be imported so that the price is high, therefore used koro pedang as an alternative food made from raw meat. The purpose of this study was to determine the level of consumer acceptance of koro sosis koro pedang. The study was conducted in 3 sub-districts in Jember district, namely Patrang, Kaliwates and Sumbersari districts. The type of research used is survey method and information obtained from consumer (respondent) by using questionnaires collected from samples to represent the population which then will be used for data processing. The level of consumer acceptance of sosis koro pedang using the method of Customer Satisfaction Index (CSI) produced is 80%, which means the consumer is very satisfied.